Spatial-Temporal Evolution Characteristics of Population Aging and its Influencing Factors in Zhongyuan Urban Agglomeration - Yang, Junping; Du, Jiusheng; Liu, Dingming; Yang, Zhipeng (International Journal of Social Sciences and Public Administration, 2025)
Taking the aging population in the Zhongyuan urban agglomeration as the research subject, using the proportion of the elderly population aged 65 and above as the primary measurement index. Methods such as standard deviational ellipse,spatial autocorrelation analysis, and the optimal parameters-based geographical detector are employed to analyze the spatial-temporal evolution and influencing factors of aging at the county scale.The results indicate that:①From 2000 to 2020, population aging in the Zhongyuan urban agglomeration intensified from northwest to southeast. The region shifted from an adult-dominated to an elderly-dominated demographic. Among them, the districts and counties under the jurisdiction of Xinyang City,Henan Province, are the most obvious. ②Population aging in the Zhongyuan urban agglomeration exhibits a strong global spatial positive correlation, with distinct local spatial clustering. The high-high cluster and low-low cluster show a trend of increasing first and then decreasing, indicating that the spatial difference of population aging has narrowed.③Factors such as fertility levels, the 2010 aging ratio, birth rates, and migration rates are the primary determinants of population aging distribution. The impact of greening and healthcare levels follows, with the influence of population, natural, and economic factors diminishing progressively.④The interaction of fertility level∩2010 aging ratio and fertility level∩greening level has a strong impact on population aging, indicating that fertility level plays a major role in the process of population aging. The research can provide an important basis for the subsequent population structure adjustment.